Aging exploration of long term multistressed HTV-silicone rubber/silica/alumina composites for high voltage insulation. (1st August 2018) - Rashid, Arooj; Amin, Muhammad; Ali, Muhammad; Khattak, Abraiz
Abstract: Aging due to environmental stresses is main problem of silicone rubber insulators. The main intention of this research is to obtain silica/alumina based HTV-SiR composite with improved aging performance. For this purpose one nano with 15% nano silica (SN) and three hybrid composites based on 20% micro silica and 2% (S2), 4% (S4) and 6% (S6) silica each along-with neat sample (SN) of High Temperature Vulcanized Silicone Rubber (HTV-SiR) are prepared and exposed to accelerated multistress laboratory aging for 13.5 lab years. For this purpose, an environmental chamber is designed and fabricated including multiple stresses such as acid rain, heat, UV radiations, salt fog etc. For aging investigation; leakage current values are recorded after each weathering cycle. Similarly, STRI classification method was applied for hydrophobicity analysis. AC dielectric strength was investigated according to ASTM D-149 standard. Fourier Transform Infrared Spectroscopy (FTIR) was performed in order to follow the structural changes in all samples. After the laboratory weathering, it was observed that all the hybrid composites showed improved leakage current, hydrophobicity, and dielectric strength. S4 and S6 showed 23.7 kV mm −1 and 23.3 kV mm −1 of dielectric strengths, both these samples showed final HC-2 hydrophobicity class and nearly 2 μ A of leakage currents. FTIR results also showed that the siloxane backbone and other important hydrocarbons remained in intact in the case of these hybrid composites. It was also emerged that higher loadings of nano-silica do not improve service life of HTV-SiR.